Blasting Vibration Analysis with Micromate Tools: Experimental Study and Characterization at the PT Semen Padang Mine - Sya’adah, Isni; Hadi, Arif Ismul; Refrizon, Refrizon; Falenia, Felly (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This research investigates the impact of vibrations produced by blasting activities at the PT Semen Padang Mine, with a focus on vibration analysis and experimental characterization using the Micromate tool. The main objective of this research is to understand the vibrations resulting from blasting, analyze the impact of variations in PVS (Peak Vector Sum) values, and evaluate the effect on the surrounding environment, especially employee housing around the mining area. The research method used involves several important stages, first of which is the use of a Micromate tool to measure the vibrations produced during the blasting process. Micromate is a tool that can record and analyze vibrations with high accuracy, thus providing reliable data for further analysis. Apart from that, this research also uses power regression analysis to understand the relationship between PVS and Scaled Distance variables. This analysis is important to determine how variations in blasting distance and intensity affect the resulting PVS values. Then, a distance analysis was carried out to obtain a PVS value below 3 mm/s, which is considered a safe threshold to prevent structural damage to the building. The research results show several important findings. Even though the measured vibration values ​​are below the Threshold Values ​​set by environmental regulations, it is important to comply with all existing regulations to avoid long-term negative impacts. The power regression analysis carried out shows that there is a significant relationship between PVS and Scaled Distance, which means that the greater the distance between the blasting point and the measurement point, the smaller the PVS value detected. The validation results of this analysis are also in accordance with the empirical data collected during the research. In addition to these main findings, this research also provides several practical recommendations. One of them is setting the explosive charge to reduce the impact of the resulting ground vibrations. These arrangements include reducing the amount of explosive per blast or changing the blasting technique to reduce vibration intensity. In conclusion, this research provides an in-depth understanding of the factors that influence vibrations from blasting in a mining context. The results of this research have important implications for the development of more accurate and effective vibration measurement methods as well as for mitigating environmental impacts caused by blasting activities. This research not only provides new insights for the mining industry but also helps in formulating better policies to protect the environment and communities around mining areas. Thus, this research contributes to ongoing efforts to achieve a balance between industrial activities and environmental sustainability.